Is Nuchal Translucency of 3.0-3.4 mm an Indication for cfDNA Testing or Microarray? - A Multicenter Retrospective Clinical Cohort Study - Rybak-Krzyszkowska, Magda (2024)
Introduction: This study aimed to evaluate the occurrence of clinically relevant (sub)microscopic chromosomal aberrations in fetuses with the nuchal translucency (NT) range from 3.0 to 3.4 mm, which would be potentially missed by cfDNA testing. Methods: A retrospective data analysis of 271 fetuses with NT between 3.0 and 3.4 mm and increased first trimester combined test (CT) risk in five cohorts of pregnant women referred for invasive testing and chromosomal microarray was performed. Results: A chromosomal aberration was identified in 18.8% fetuses (1:5; 51/271). In 15% (41/271) of cases, trisomy 21, 18, or 13 were found. In 0.7% (2/271) of cases, sex chromosome aneuploidy was found. In 1.1% (3/271) of cases, CNV >10 Mb was detected, which would potentially also be detected by genome-wide cfDNA testing. The residual risk for missing a submicroscopic chromosome aberration in the presented cohorts is 1.8% (1:54; 5/271). Conclusion: Our results indicate that a significant number of fetuses with increased CT risk and presenting NT of 3.0-3.4 mm carry a clinically relevant chromosomal abnormality other than common trisomy. Invasive testing should be offered, and counseling on NIPT should include the test limitations that may result in NIPT false-negative results in a substantial percentage of fetuses.